The role of aortic carboxypeptidase-like protein (ACLP) in 3T3-L1 preadipocyte and adipocyte function - Gusinjac, Arjeta (University of Ottawa (Canada), 2009)
Aortic carboxypeptidase-like protein (ACLP) is a 175kDa secreted protein that is downregulated with adipogenesis. I engineered 3T3-L1 preadipocytes that overexpressed ACLP protein and sustained the overexpression with differentiation. I assessed the role of sustained ACLP overexpression on 3T3-L1 adipogenesis, with a focus on possible ACLP interaction with collagen-I during differentiation. ACLP overexpression did not affect 3T3-L1 adipogenesis under standard cell culture conditions ACLP overexpression did not affect subconfluent preadipocyte proliferation, apoptosis in serum-supplemented preadipocytes, or serum-deprived preadipocyte cell death. Sustained ACLP overexpression did not affect collagen I/III protein expression, or the activity of matrix metalloproteinase (MMP)-2 and MMP-9 extracellular degrading enzymes. However, sustained ACLP overexpression on collagen-I coated dishes inhibited the expression of three key differentiation markers, peroxisome proliferator-activated receptor gamma, CCAAT enhancer-binding protein alpha and fatty acid synthase and decreased insulin-stimulated Akt/protein kinase B phosphorylation. This suggests that a collagen-I-rich environment is necessary for ACLP to alter preadipocyte function.
Keywords: Biology, Molecular.